Transcatheter aortic valve replacement in patients with severe aortic stenosis reduced the frequency of intradialytic hypotension - Makoto Saigan; Masaki Miyasaka; Tasuku Nagasawa; Masataka Taguri; Natsuko Satomi; Manami Watahiki; Masaki Nakashima; Yusuke Enta; Yusuke Toki; Yoshiko Munehisa; Jun Ito; Yukihiro Hayatsu; et al. (Scientific Reports, 2024)
Abstract Intradialytic hypotension (IDH) is a common complication during hemodialysis that increases cardiovascular morbidity and mortality. Aortic stenosis (AS) is a cause of IDH. Transcatheter aortic valve replacement (TAVR) has become an established treatment for patients with severe AS. However, whether TAVR reduce the frequency of IDH has not been investigated. This study aims to verify the efficacy of TAVR for reduction of the frequency of IDH. Consecutive hemodialysis patients who underwent TAVR at Sendai Kosei Hospital from February 2021 to November 2021 with available records 1 month before and 3 months after TAVR were included in the study. IDH was defined as a decrease in systolic blood pressure by 20 mmHg or a decrease in the mean blood pressure by 10 mmHg associated with hypotensive symptoms or requiring intervention. Patients with ≥ 3 episodes of IDH in ten hemodialysis sessions comprised the IDH group. Overall, 18/41 (43.9%) patients were classified into the IDH group. In ten hemodialysis sessions, IDH events were observed 2.1, 4.3, and 0.4 times in the overall cohort, IDH group, and non-IDH group, respectively. After TAVR, the incidence of IDH decreased from 43.2 to 10.3% (p < 0.0001) and IDH improved significantly in 15 patients in the IDH group. The result suggested that severe AS was the major cause of IDH in this cohort, and TAVR may be an effective treatment option for reduction of the frequency of IDH in patients with severe AS.